2001
DOI: 10.1152/jappl.2001.90.5.1770
|View full text |Cite
|
Sign up to set email alerts
|

Age, sex, race, initial fitness, and response to training: the HERITAGE Family Study

Abstract: Effects of age, sex, race, and initial fitness on training responses of maximal O(2) uptake (VO(2 max)) are unclear. Data were available on 435 whites and 198 blacks (287 men and 346 women), aged 17-65 yr, before and after standardized cycle ergometer training. Individual responses varied widely, but VO(2 max) increased significantly for all groups. Responses by men and women and by blacks and whites of all ages varied widely. There was no sex difference for change (Delta) in VO(2 max) (ml. kg(-1). min(-1)); w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
170
4
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(195 citation statements)
references
References 17 publications
18
170
4
3
Order By: Relevance
“…Our results are in line with previous studies in healthy non-CF people, showing an inverse relationship between the levels of fitness at baseline and the magnitude of improvement in V9O 2 ,peak and suggesting a normal training response in CF [5,13]. These findings are of particular interest because NIXON et al [10] and PIANOSI et al [19] have shown that the likelihood of survival is greater in CF with a higher level of aerobic fitness.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are in line with previous studies in healthy non-CF people, showing an inverse relationship between the levels of fitness at baseline and the magnitude of improvement in V9O 2 ,peak and suggesting a normal training response in CF [5,13]. These findings are of particular interest because NIXON et al [10] and PIANOSI et al [19] have shown that the likelihood of survival is greater in CF with a higher level of aerobic fitness.…”
Section: Discussionsupporting
confidence: 92%
“…Healthy people with lower peak oxygen uptake (V9O 2 ,peak) can improve more than those who have already trained or are physically active [5]. In subjects with CF, a positive relationship between physical activity and V9O 2 ,peak has been found [6,7].…”
mentioning
confidence: 99%
“…For example, the HERITAGE Family Study investigated intra-individual variation in responsiveness to regular exercise training in healthy, sedentary individuals and showed that lower initial fitness values were associated with greater relative changes. 14 There are only few studies that have investigated the response to an exercise program with respect to initial fitness level in diseased individuals. A study among cystic fibrosis patients showed that a 6-week exercise program led to significantly different training responses between initially fit and unfit groups, with greater improvements in subjects with a lower initial fitness level.…”
Section: Introductionmentioning
confidence: 99%
“…The study suggested that race has no significant effect on the response of VO 2 max to exercise training [17].…”
Section: Discussionmentioning
confidence: 81%